2014
DOI: 10.1002/pro.2460
|View full text |Cite
|
Sign up to set email alerts
|

Membrane protein stability can be compromised by detergent interactions with the extramembranous soluble domains

Abstract: Detergent interaction with extramembranous soluble domains (ESDs) is not commonly considered an important determinant of integral membrane protein (IMP) behavior during purification and crystallization, even though ESDs contribute to the stability of many IMPs. Here we demonstrate that some generally nondenaturing detergents critically destabilize a model ESD, the first nucleotide-binding domain (NBD1) from the human cystic fibrosis transmembrane conductance regulator (CFTR), a model IMP. Notably, the detergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 98 publications
1
85
0
Order By: Relevance
“…To assess molecular characteristics of the Xkr8 protein, PLB985 cells (PLB) not expressing Xkr8 (14) were transformed with Flagtagged human Xkr8 (hXkr8). Because the stability and subunit structure of membrane proteins is often regulated by Ca 2+ and detergent (19,20), PLB-hXkr8 was lysed in different detergents (CL47 or CL48) with mild and intermediate stringency (21) containing 0.5 mM EGTA or 1.0 mM Ca 2+ and separated by BN-PAGE. Western blot with anti-Flag showed that hXkr8 lysed in CL47 behaved as a large complex in the presence or absence of Ca 2+ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess molecular characteristics of the Xkr8 protein, PLB985 cells (PLB) not expressing Xkr8 (14) were transformed with Flagtagged human Xkr8 (hXkr8). Because the stability and subunit structure of membrane proteins is often regulated by Ca 2+ and detergent (19,20), PLB-hXkr8 was lysed in different detergents (CL47 or CL48) with mild and intermediate stringency (21) containing 0.5 mM EGTA or 1.0 mM Ca 2+ and separated by BN-PAGE. Western blot with anti-Flag showed that hXkr8 lysed in CL47 behaved as a large complex in the presence or absence of Ca 2+ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The shorter chain detergents have higher CMC values, and observed differences in ATPase activity might be due to increased detergent exposure at the necessarily higher detergent concentrations used during chromatography. Purification of CFTR in lysoPC, despite its low CMC, resulted in quite low reconstituted ATPase activity, suggesting loss of conformation such as that demonstrated when isolated NBDs of CFTR were exposed to this detergent [14]. Among widely used detergents, MNGs, DDM, and Chaps preserved the highest CFTR ATPase activities.…”
Section: Resultsmentioning
confidence: 99%
“…Another unique feature of CFTR is the R region whose phosphorylation regulates channel gating through an unknown mechanism [13]. CFTR NBDs exhibit conformational sensitivity to many detergents, likely contributing to the great difficulty in recovering active purified protein [14]. Purification of active CFTR from insect and yeast cells using perfluorooctanoate [15] or lysolipid [1618] has been reported, but CFTR purified with these detergents in other laboratories has proven too unstable for detailed biophysical characterization.…”
Section: Introductionmentioning
confidence: 99%
“…A study of the CFTR-NBD1 indicated that ionic detergents could destabilize this domain [40]. Using NBD1 as a surrogate for full-length CFTR, the authors used differential scanning calorimetry (DSC) to investigate the effect of different detergents on the unfolding temperature of the purified protein.…”
Section: Purification Of Cftrmentioning
confidence: 99%